Effect of Dung Quantity and Quality on Greenhouse Gas Fluxes From Tropical Pastures in Kenya. Issue 10 (29th October 2018) - Zhu, Yuhao; Merbold, Lutz; Pelster, David; Diaz‐Pines, Eugenio; Wanyama, George Nandhoka; Butterbach‐Bahl, Klaus
Abstract: To improve estimates of agricultural greenhouse gas emissions in sub‐Saharan Africa, we measured over six individual periods of 25–29 days fluxes of methane (CH4 ), carbon dioxide (CO2 ), and nitrous oxide (N2 O) with subdaily time resolution from dung patches of different quality (C/N ratio: 23–41) and quantity (0.5 and 1.0 kg) on a Kenyan rangeland during dry and wet seasons. Methane emissions peaked following dung application, whereas N2 O and CO2 fluxes from dung patches were similar to fluxes from rangeland soils receiving no N additions. Greenhouse gas emissions scaled linearly with dung quantity during both seasons. Dung with a low (23) C/N ratio produced up to 10 times more CH4 than dung with a high (41) C/N ratio. Overall, CH4 emission factors (EFs) ranged from 0.001 to 0.042%, lower than those derived in temperate regions. Cumulative CO2 and N2 O emissions were similar for all treatments across the different seasons. The N2 O EF ranged from 0 to 0.01%, less than 1% of the Intergovernmental Panel on Climate Change Tier 1 default EF (2%) for N2 O emissions from dung and urine patches, likely because of the low dung N content (9.7–16.5 g N kg −1 dry matter). However, these results were consistent with the updated cattle dung EF (0.2%) developed for Kenya in 2016/2017 (EF database ID# 422665). In view of the wide range of climates, soils, and management practices across sub‐Saharan Africa, development of robust GHG EFs from dung patches for SSA requires additional studies. Plain Language Summary: With regard to the agricultural sector, livestock production systems are the dominant greenhouse gas (GHG) source. A significant part of emissions due to livestock production is linked to GHG emissions from dung patches on rangelands. While this source is rather well constrained for countries with developed economies, little is known about GHG emissions from dung patches in developing countries, specifically for countries in Sub‐Saharan Africa. Based on own measurements and an extensive literature review we show that GHG emissions from dung patches are likely highly overestimated as poor feed quality and differences in environmental conditions strongly limit GHG emissions. Our work calls for a revision of emission estimates from this important GHG source for developing countries. Key Points: N2 O fluxes from dung patches on rangeland in Kenya are only 1% of current IPCC estimate Low emissions are very likely due to low N content of the dung, which results from poor feeds Emission factor for dung patches needs to be revised, specifically for livestock systems in developing countries